Trade uncertainty and U.S. bank lending - Ricardo Correa; Julian Di Giovanni; Linda S. Goldberg; Camelia Minoiu (Federal Reserve Bank of New York, 2023)
This paper uses U.S. loan-level credit register data and the 2018-2019 Trade War to test for the effects of international trade uncertainty on domestic credit supply. We exploit cross-sectional heterogeneity in banks' ex-ante exposure to trade uncertainty and find that an increase in trade uncertainty is associated with a contraction in bank lending to all firms irrespective of the uncertainty that the firms face. This baseline result holds for lending at the intensive and extensive margins. We document two channels underlying the estimated credit supply effect: a wait-and-see channel by which exposed banks assess their borrowers as riskier and reduce the maturity of their loans, and a financial frictions channel by which exposed banks facing relatively higher balance sheet constraints contract lending more. The decline in credit supply has real effects: firms that borrow from more exposed banks experience lower debt growth and investment rates. These effects are stronger for firms that are more reliant on bank finance.
Keywords: F34; F42; G21; 330; trade uncertainty; bank loans; trade finance; global value chains; trade war